Fullerene-diamond transformation under irradiation with charged particles (review) - Khoruzhiy, V.M. (Вопросы атомной науки и техники, 2001)
For the first time nanodiamonds were obtained at the Max Planck Institute (Stuttgart, Germany) in 1997. Dr Banhart and his group investigated transformation of fullerenes into diamond under electron beam irradiation in the electron microscope (electron beam energy is 1.25 MeV). Next experiment in MPI (Stuttgart) hows that much larger amounts of diamond can be obtained if uses ions from linac instead of electrons as irradiating particles. A fullerene sample was irradiated with 3 MeV Ne+ from the pelletron accelerator. Under the ion irradiation, the temperature of a sample reached 1000-1400K. The maximum range of 3 MeV Ne+ ions in a sample is about 2 µm.